(3GdeYGjjQ GdeMGSHjI GdeUQjI heTcdGJ GdJWHjb (B/s - (3YHO QHg eMeO, eMeO eMehOs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3GdeYGjjQ GdeMGSHjI GdeUQajI ,GdEWGQ GdfXQj ddeMGSHI,GdEWGQ GdYGe ddeYGjjQ GdeMcejI GdeUQjI,eYGjjQ eMGSHI NGUI HGdEaUGM GdeMGSHj ,eYGjjQ eMGSHjI NGUI HGdbjGS hGdJbjje GdeMGSHj (B-(3OQGSI HYV eTGcd GdbjGS hGdJbjje GdeMGSHj ,GdJZjjQGJ GdeMGSHjI ,GdCUhd GdKGHJI hGedGcGJgG (B-(3GdbjGS GdeMGSHj dddCHQGO ,GdbjGS GdeMGSHj ddeUQha hGdeNRhf ,GdbjGS GdeMGSHj dJcdaI GdEaJQGV ,GdeMGSHI Yf YedjGJ GdJCLjQ GdJehjdj ,bGFeI GdJOabGJ GdfbOjIs
(3GdeQGLY U(B.256s
Keywords: (3GdeMGSHI (B- (3eUQs; (3GdeYGjjQ GdeMGSHjIs